Changing Mission, Strengthened Focus: A New Use for the Current Periodicals Room at the University of California, Santa Cruz. - Catherine Soehner; Christy Hightower; Wei Wei (Issues in Science and Technology Librarianship, 2005)
The Science & Engineering Library at UC Santa Cruz was built in 1991 and included a beautiful room dedicated to a print collection of current periodicals. During the past four years we have systematically canceled all print journals for which there was an electronic counterpart, thus diminishing the number of journals in the Current Periodicals Room. During a strategic planning effort, the Library determined that it should be identified as the "Information Center" of the campus and be the "destination of choice" for students, faculty, staff, and members of our greater community even in this digital age. As a first step toward realizing this goal, the library staff began a lecture series entitled Synergy: Explorations in Science and Society, held in the Current Periodicals Room. This new lecture series highlights research, teaching, and grants in science and engineering at UCSC and brings these efforts to the attention of the UCSC and greater Santa Cruz community. The response to this lecture series has been overwhelmingly positive with record attendance. This venture marks the beginning of a successful move toward integrating the library further into the mission of the University and further increases the library's connection with its faculty. [ABSTRACT FROM AUTHOR]